The application of garlic (Allium sativum) peel on African catfish (Clarias gariepinus) against Aeromonas hydrophila infection - Nordin, Eirna Liza; Saad, Che Roos; Abu Hassim, Hasliza; Abd Karim, Murni Marlina (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2016)
This study aim to investigate the efficacy of dietary doses of garlic (Allium sativum) peel on disease resistance and the duration of protection of African catfish (Clarias gariepinus) juveniles against Aeromonas hydrophila infection. African catfish juveniles were fed twice daily for 4 weeks with 20 gkg-1 of garlic peels incorporated into fish formulated diet. Meanwhile 0 g of peels was served as control. After 4 weeks of post feeding, 15 fish were randomly selected for challenge with 108 cell/mL of A. hydrophila. During the challenge the fish were not fed with dietary of garlic. The duration of protection was observed at 7, 14 and 21 days following infection. The results demonstrated that dietary garlic peels provided protection toward African catfish against A. hydrophila after 14 days post feeding and slightly reduced protection after 21 days of post feeding. Significantly higher survival rate were recorded in dietary garlic peels (66%, 86% and 42%) when compared with the control. The result indicated that garlic peels able to enhance disease resistant of African catfish towards A. hydrophila infection.